High-throughput analysis of pesticides in minor tropical fruits from Colombia. (15th May 2019) - Varela-Martínez, Diana Angélica; González-Curbelo, Miguel Ángel; González-Sálamo, Javier; Hernández-Borges, Javier
Highlights: QuEChERS-GC–MS/MS was applied for the extraction of 35 multiclass pesticides. Four tropical fruits cultivated and exported in Colombia were selected. The use of analyte protectants and matrix effects were evaluated. Acceptable recovery values were obtained being the LCL 5 µg/kg. Samples of each type of tropical fruit were analysed. Abstract: In this work, a method has been applied and validated for the determination of a group of 35 multiclass pesticides in the minor tropical fruits rose apple/pomarrosa ( Syzygium malaccense ), starfruit/carambola ( Averrhoa carambola ), yoyomo ( Spondias purpurea ) and papayuela ( Vasconcellea pubescens ) cultivated and exported in Colombia. The AOAC 2007.1 QuEChERS method, that uses an acetic acid/acetate buffer, was applied together with gas chromatography coupled to a triple quadrupole mass spectrometer. The method was validated in terms of calibration, recovery at three levels of concentration and matrix effects (MEs). A mixture of analyte protectants was also used. A good linearity was obtained in all cases, while the study of the ME revealed the need of developing matrix-matched calibration for many pesticides. Recovery values were in the range 70–120% with relative standard deviation values less than 20% for most of the pesticides studied. The lowest calibration level was 5 µg/kg. Several samples of each type were analysed.